Analisis Sistem Informasi Manajemen di PT. Bank Negara Indonesia - Pagan, Muasir (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The purpose of the research is to be able to deduce problems relating to Management Information Systems. Fulfilling Office Administration Duties. Can implement Management Information Systems in the real world after understanding it. Management Information System (SIM) is an integrated human/machine system that provides information to support the operational functions of management and decision-making within an organization. Management information systems are described as a pyramid building where the underlying layer consists of information, transaction descriptions, status explanations, and so on. The next layer consists of information resources in support of day-to-day management operations. The three layers consist of information system resources to assist tactical planning and decision-making for management control. The system uses computer hardware and software, guideline procedures, management and decision models, and a "data base".